Bank competition, government intervention and SME debt financing. Issue 4 (20th November 2017) - Du, Jianhua; Bian, Chao; Gan, Christopher
Abstract : Purpose: The purpose of this paper is to examine the effects of the government intervention and bank competition on small and medium enterprise (SME) external debt financing in Chinese capital market. Design/methodology/approach: This study uses ordinary least squares with standard errors clustered at the firm level. In addition, the authors use the dynamic system generalized method of moments to address the possible endogeneity issue in the regressions. Findings: Using a sample of 908 firms from 2000 to 2010, the authors found that SMEs are more likely to access bank loans only in regions with higher level of government intervention than median government intervention. Further, the result shows that the government is motivated to help SMEs to obtain more external debt in regions where the level of bank competition is lower than the median bank competition index. Last, the authors found evidence that firms with politically connected CEOs are likely to access bank loans. Research limitations/implications: This paper highlights that government intervention enables the SMEs to secure more bank loans. Second, the authors' results imply that the government is motivated to help SMEs to obtain more external debt in regions with low level of bank competition. Originality/value: This study contributes to the current literature by revealing that government intervention is the driving force alleviating SMEs' constraints in accessing external financing. Second, this study finds the evidence to supports the argument that government has a strong motive to help SMEs to secure long-term credits for political purpose (Fan et al., 2012), when the level of bank competition is low (Berger and Udell, 2006).